Using Problem-Based Learning to Develop EFL Pre-service Teachers’ Intercultural Awareness - Misdi Misdi; Ratna Andhika Mahaputri (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
This article reports an on-going research project dealing with intercultural issue that has conducted in the department of English education in a private university. In the framework of case study, this study attempts to describe how students were involved and shared their insights of intercultural learning in the classroom. Forty EFL pre-service teachers were recruited and involved in the current study. The data were drawn from the classroom observation. From the categorized data, critical incidents were captured and interpreted. The findings show the students’ sense of intercultural awareness developed. It concludes this problem-based learning provides authentic and meaningful learning as the students were engaged in real-lives related projects of intercultural exchangesArtikel ini merupakan sebagian laporan dari riset tentang kompetensi lintas budaya yand dilaksanakan di sebuah perguruan tinggi swasta di Cirebon-Indonesia. Dalam kerangka studi kasus, riset ini bertujuan untuk mendeskripsikan bagaimana mahasiswa calon guru terlibat dalam diskusi kasus lintas budaya yang diberikan di dalam kelas. Empat puluh mahasiswa calon guru bahasa Inggris direkrut dan terlibat dalam riset. Semua partisipan telah melalui dan memberikan persetujuan merekan untuk secara suka rela terlibat dalam proyek riset ini. Semua data dikumpulkan dari hasil observasi kelas dan hasilnya diintepretasokan dari setiap critical incident yang muncul. Hasil riset menjelaskan bahwa kemampuan komunikasi lintas budaya mahasiswa semakin terbangun. Hasil ini berkesimpulan bahwa problem-based learning merupakan pembelajaran yang penuh kebermaknaan dan pembelajaran yang otentik yang membuat mahasiswa terlibat dalam proyek-proyek yang menyentuh kehidupan langsung terkait dengan interaksi lintas budaya